Obesity and associated cardiometabolic risk among women from Tripura - A Northeastern State of India - Purnajita Sen; Sandeep Das; Samrat Hore; Surajit Bhattacharjee; Dipayan Choudhuri (Wolters Kluwer Medknow Publications, 2017)
Introduction: Cardiometabolic health status of women is a serious public health concern. Markers of body fat content and their distribution are important indicators of cardiometabolic health risk in participants. In addition, socio-demographic status plays a determinant role. The aim of the study was to evaluate the influence of adiposity markers and socio-demographic determinants on various cardiovascular and metabolic risk factors in Indian women. Materials and Methods: The study was conducted on 388 women (age 25-65 years) from Tripura, a Northeastern state of India. Various obesity and atherogenic markers such as body mass index (BMI), waist circumference (WC), waist-hip ratio, waist - height ratio, high density lipoprotein-cholesterol (HDL-C)/total cholesterol, HDL-C/low density lipoprotein cholesterol, triglyceride/HDL-C ratio and traditional cardiometabolic risk factors such as high blood pressure, dyslipidemia, and glucose intolerance were evaluated in participant. The socio-demographic status included the level of education and monthly family income. Results: The cardiometabolic risk in postmenopausal women were higher than premenopausal women. The risk increases with age in both groups. Women with lower educational level and higher income group were found to be prone to higher cardiometabolic risk. Receiver operating characteristics analysis revealed central obesity marked by increased WC was a better predictor of cardiometabolic risk than general obesity marked by increased BMI. Conclusion: The cardiometabolic risk among both premenopausal and postmenopausal women are associated with central obesity which can be predicted by increased WC in the subject. Socio-demographic status of the participant plays a definitive role in determining cardiometabolic risk in women.